Hydroponics-Based Romaine Lettuce Production in Peri- Urban Areas: Market Competitiveness Study in Greater Bandung Metropolitan Region - Adnan Rivaldo, Muhammad Is'raj (Politeknik Siber Cerdika Internasional, 2025)
This study investigated the market competitiveness of hydroponics-based romaine lettuce production in peri-urban areas of the Greater Bandung Metropolitan Region, Indonesia, and addressed critical knowledge gaps regarding economic viability and strategic positioning of controlled environment agriculture in rapidly urbanizing tropical contexts. Employing a comprehensive mixed-methods approach, the research integrated technical performance data from fifteen commercial hydroponic farms over six production cycles spanning 18 months, detailed economic analysis of production costs and profitability indicators, competitive market assessment through Porter's Five Forces and SWOT frameworks, and consumer preference surveys administered to 384 respondents across diverse socioeconomic segments. Results demonstrated that hydroponic systems achieved superior technical performance with 35.6% higher yields, 87.3% marketable quality rates, and 11.4 annual production cycles compared to conventional cultivation, translating into substantial economic returns averaging 58.4% ROI and 2.12 revenue-cost ratios despite capital requirements nearly five times higher than traditional systems. Market analysis revealed that competitive advantage emerged through integrated management of production efficiency, premium retail channel access commanding 130.7% price premiums, and medium-scale operations, with consumer willingness to pay significantly influenced by quality perceptions, food safety concerns, and information provision. The study concludes that hydroponic romaine lettuce production represents an economically viable and competitive agricultural strategy in peri-urban metropolitan regions when technical proficiency, strategic marketing, and adequate scale are simultaneously achieved, though success requires coordinated support addressing knowledge gaps, market access barriers, and capital constraints.